Local asset management: Overview of policy implementation. Study at the Bandung District Health Office - Mochamad Guntur; Arifianti, Ria; Candradewini (Technium Social Sciences Journal, 2021)
The purpose of this research is to find out and describe in detail how the Local Asset Management policy is implemented at the Bandung District Health Office. The research method used is a descriptive qualitative method with a case study approach. Data collection techniques are carried out by interviewing, observing, and recording documents related to local asset management. The data obtained are then analyzed qualitatively by examining all data that has been collected with policy implementation indicators, namely policy standards and targets, resources, communication between implementing agencies, characteristics of the implementing agency, social, economic, and political environment, and the attitudes of the implementers or dispositions. The results showed that the implementation of local asset management policies at the Bandung District Health Office had been running but was not optimal. There are several problems such as the lack of fulfillment of the required Local Asset even though the planning and budgeting activities have been carried out, the attitude of former Health Service employees who are not supportive because they do not return the assets used during their tenure, there is the local asset that does not have proof of ownership, storage warehouse which is less orderly because improper goods are not destroyed, incomplete inventory and ineffective procedures for eliminating local asset. This issue arises because the goods organizational management, as the policy’s implementer, lacks the necessary human resources and attitudes.